PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK BERBASIS KONTEKSTUAL TERINTEGRASI POTENSI LOKAL WISATA LAUT - Harsiwi, Nova Estu; Adinanda Siswoyo, Andika; Ayu Rahmawati, Ika (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
This research is to produce thematic learning tools based on a contextual approach by integrating the local potential of Jumiang Beach Tourism. This study uses a 4-D development model developed by Thiagarajan. The research subjects were grade 4 students of UPTD SDN Tanjung 3 Pamekasan. The research instruments used included observation sheets, interview guides, and tests. Based on the results of the study, it was found that the validity of the learning device showed that the score of the design validation results was at 88%, and the material validation was 92.6%. So that the average student validation reaches 90%. The results of the practicality of learning devices are in the attractive category with a score of 86%, and the effectiveness of students reaching 85% is in the effective category. Based on these conclusions, a thematic learning tool based on an integrated contextual approach that is valid, practical and effective for use in elementary schools.